2017
DOI: 10.1155/2017/4898467
|View full text |Cite
|
Sign up to set email alerts
|

The Propagation of Thermoelastic Waves in Anisotropic Media of Orthorhombic, Hexagonal, and Tetragonal Syngonies

Abstract: The investigation of wave propagation in elastic medium with thermomechanical effects is bound to have important economic implications in the field of composite materials, seismology, geophysics, and so on. In this article, thermoelastic wave propagation in anisotropic mediums of orthorhombic and hexagonal syngony having heterogeneity along -axis is studied. Such medium has second-order axis symmetry. By using analytical matriciant method, a set of equations of motions in thermoelastic medium are reduced to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In papers [12,13], the general form a matricant structure is similar to the (31) and the exact solution of the system of differential equations (9), which describes the propagation of thermoelastic waves in anisotropic medium was formulated. The system of differential equations is as described (23).…”
Section: Solution Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…In papers [12,13], the general form a matricant structure is similar to the (31) and the exact solution of the system of differential equations (9), which describes the propagation of thermoelastic waves in anisotropic medium was formulated. The system of differential equations is as described (23).…”
Section: Solution Of the Problemmentioning
confidence: 99%
“…The wave propagation in the thermoelastic anisotropic medium have been investigated by using a matricant method, for instance wave propagation waves in liquid crystals and in thermoelastic medium [11][12][13][14][15][16][17]. In the paper [18], authors consider the propagation of Rayleigh surface waves in a functionally graded isotropic thermoelastic half-space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the method matriciant [12] EM wave propagation in elastic, thermoelastic anisotropic, anisotropic dielectric media, in anisotropic plates, and with magnetoelectric effect have been investigated [13][14][15][16]. The matriciant method is also employed to investigate propagation of spin waves, the waves in liquid crystals and wave propagation in thermoelastic media [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that these SEV are effectively generated by the attenuated total reflection method. Processes in elastic anisotropic and anisotropic dielectric media and propagation of waves in anisotropic plates, electromagnetic waves in media with magnetoelectric effect [14][15][16][17], and waves in liquid crystals and thermoelastic media [18][19][20] were considered in [13] using the matricant method. Results of uniform description of wave processes in media with different physicomechanical properties were reported at the XVth All-Russian School-Seminar "Physics and Application of Microwaves" named after A. P. Sukhorukov (Waves-2016) [21].…”
Section: Introductionmentioning
confidence: 99%